(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Exanthemic diseases remain an urgent medical problem in the Khorezm region. The article presents the results of a retrospective study of the prevalence of exanthemic diseases among the population of the Khorezm region of the Republic of Uzbekistan. The study covers the period 2024 and is based on an analysis of the medical records of 50 patients aged 1 to 50 years who sought medical help with symptoms of exanthema.